Relationship between baseline platelet-to-red blood cell distribution width ratio and all-cause mortality in non-traumatic subarachnoid hemorrhage: A retrospective analysis of the MIMIC-IV database - Yang Liu; Yi Shi; Pengzhao Zhang; Mengyuan Xu; Jiaqi Zhang; Jing Xia; Shaojie Guo; Gaofeng Li; Guang Feng (PLoS ONE, 2025)
Objective The study aimed to evaluate the relationship between baseline platelet-to-red blood cell distribution width ratio (PRR) and mortality in critically ill patients with non-traumatic subarachnoid hemorrhage (SAH). Methods This cohort study of adults with non-traumatic SAH used Medical Information Mart for Intensive Care (MIMIC-IV) data from 2008–2022 admissions at the Intensive Care Unit (ICU). We collected the PRR levels at admission and determined the all-cause death rates for the ICU and hospital. Cox proportional hazards models were utilized to analyze the association between baseline PRR level and all-cause mortality. Kaplan–Meier survival curve analysis was used to examine the consistency of these correlations. Restricted Cubic Splines (RCS) analysis was used to determine the relationship curve between all-cause mortality and PRR level and examine the threshold saturation effect. To evaluate the consistency of correlations, interaction and subgroup analyses were also conducted. Results A total of 1056 patients with non-traumatic SAH were included in this study. All-cause mortalities in the ICU and hospital were 14.8% (156/1056) and 18.6% (196/1056), respectively. Compared to individuals with lower PRR Q1(≤12.67), the adjusted HR values in Q2 (12.68–15.99), Q3 (16.00–19.41), and Q4 (≥19.42) were 0.61 (95%CI:0.40–0.92, p = 0.017), 0.60 (95%CI: 0.39–0.92, p = 0.020), and 0.60 (95% CI:0.39–0.93, p = 0.019), respectively. Kaplan–Meier analysis showed that patients with low PRR levels had significantly higher ICU and in-hospital mortality (p < 0.001). The association between the PRR level and ICU and in-hospital mortality exhibited a non-linear relationship (p < 0.05). The threshold breakpoint value of 22.6 was calculated using RCS analysis. When the PRR level was lower than 22.6, the risk of ICU and in-hospital mortality rates decreased with an HR of 0.91 (95%CI: 0.88–0.94, p < 0.001) and 0.94 (95%CI: 0.92–0.96, p < 0.001), respectively. When the PRR level was higher than 22.6, the risk of ICU mortality (HR = 1.03, 95% CI: 0.97–1.10, p = 0.312) and in-hospital mortality (HR = 1.01, 95%CI: 0.95–1.08, p = 0.693) almost hardly increased with the increase in the PRR level. The interaction between the PRR and all subgroup factors was analyzed, and significant interactions were not observed. Conclusion There was a non-linear connection between the baseline PRR level and in-hospital mortality. A low level of PRR could increase the risk of death in participants with non-traumatic SAH.